New orthorhombic sodium iron(+2) titanate. Issue 4 (March 2020) - Shukaev, Igor L.; Butova, Vera V.; Chernenko, Sergey V.; Pospelov, Andrey A.; Shapovalov, Victor V.; Guda, Alexander A.; Aboraia, Abdelaziz M.; Zahran, Heba Y.; Yahia, Ibrahim S.; Soldatov, Alexander V.
Abstract: The set of compositions with Fe 2+ in the system Nax Fex/2 Ti2–x/2 O4 has been prepared by solid-state reactions in the inert atmosphere at 1050 °С. The oxidation state of iron was confirmed using the XANES method. Na0.88 Fe0.44 Ti1.56 O4 is the new four-element compound in Na2 O–"FeO"–TiO2 system. According to the X-ray powder data, it is orthorhombic, Pnma, a = 9.3624(1), b = 2.96718(4), c = 11.3435(1) Å and has the same structure as Na0.9 Fe0.9 Ti1.1 O4 with Fe 3+ . The structure was refined by the Rietveld method. The 3D-framework of (Fe, Ti)O6 octahedra contains quadruple rutile-like chains and sodium ions in double tunnels. Fe/Ti partial ordering in the framework and sodium distribution in the tunnels were studied additionally using the method of bond valence sums and Voronoi tessellation. The structure and composition of Na0.88 Fe0.44 Ti1.56 O4 make it a promising material for cathode application.